2005
DOI: 10.1007/s11199-005-3736-4
|View full text |Cite
|
Sign up to set email alerts
|

Turkish Social Work Students’ Attitudes Toward Sexuality

Abstract: The purpose of this research was to determine the attitudes of social work students in Turkey toward sexuality. According to the findings, gender differences, talking about sexuality, and having an active sex life, affect liberality about sexuality. Religious beliefs have a significant impact on attitudes, and our data show that Turkish social work students were relatively sexually inexperienced and conservative. However, they were more accepting and liberal for others' sexual preferences than for their own.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 12 publications
7
39
1
1
Order By: Relevance
“…Formal sexual education is very important in promoting positive attitudes and behaviors about sexuality [25]. In Turkey, sexual education is only provided in a limited number of medical settings and the education is mainly very restricted and informal.…”
Section: Discussionmentioning
confidence: 99%
“…Formal sexual education is very important in promoting positive attitudes and behaviors about sexuality [25]. In Turkey, sexual education is only provided in a limited number of medical settings and the education is mainly very restricted and informal.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual orientation is another factor determining attitude towards gender differences in addition to the secondary position of women. The research showed that female preservice teachers were more tolerant to sexual orientation differences than male participants (Duyan & Duyan, 2005;Gelbal & Duyan, 2006;Sakallı, 2002;Şah, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The literature also reveals that female preservice teachers are more likely to tolerate sexual orientation differences compared to male participants (Duyan and Duyan, 2005;Gelbal and Duyan, 2006;Sakallı, 2002;Şah, 2012). Moreover, female participants were more likely to tolerate diverse political identities because they scored higher on democratic attitudes compared to male participants (Aydemir and Aksoy, 2010;Çermik, 2013;Genç and Kalafat, 2007;Gömleksiz and Kan, 2008;Saracaloğlu, Evin and Varol, 2004).…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%
“…Kadının ikincil konumu yanında toplumsal cinsiyet tutumlarını belirleyen bir diğer etken ise cinsel yönelim farklılıklarıdır. Yapılan araştırmalar kadın öğretmen adaylarının cinsel yönelim farklılıkları konusunda da erkek katılımcılara oranla daha toleranslı olduklarını ortaya koymaktadır (Duyan ve Duyan, 2005;Gelbal ve Duyan, 2006;Sakallı, 2002;Şah, 2012).…”
Section: Tartışma Ve Sonuçunclassified